Glucoamylase Production by Aspergillus awamori KT-11 In Solid State Fermentation Using Cassava Peel as Substrate - Perwitasari, Urip; Nuryati, Nuryati; Melliawati, Ruth; Yopi, Yopi (BRIN, 2017)
Cassava has long been known as one of the main staple food in Indonesia. Whereas the cassava peel contains starch of approximately 72%, it is still underrated as a carbohydrate source for fermentation.The utilization of cassava peel as a substrate in solid state fermentation potentially replaces rice as a carbon source leading to more cost-effective production. This study aims at producing glucoamylase by means of solid state fermentation using Aspergillus awamori KT-11 and cassava peel as substrate. The study demonstrated that medium composition and drying technique affected the production of glucoamylase. The highest glucoamylase activities were identified when cassava peel and mineral media was used in fermentation, compared to only cassava peel; the combination of cassava peel, mineral, and rice bran; rice media or a mixture of rice, mineral and rice bran. Freeze-dried glucoamylase, furthermore, exhibited higher specific activity in contrast to the oven-dried one, with 452 U/mL and 365 U/mL, respectively. In conclusion, cassava peel plus mineral is a better substrate for glucosamine production by A. awamori KT-11 in solid state fermentation. Besides, powdered glucoamylase had been demonstrated to be capable of hydrolyzing starch-based biomass.